The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1001/jamaoto.2013.3395
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Voice and Swallowing Parameters After Endoscopic Total and Partial Arytenoidectomy for Bilateral Abductor Vocal Fold Paralysis

Abstract: clinicaltrials.gov Identifier: NCT01824849.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 12 publications
3
30
0
2
Order By: Relevance
“…La elección de esta técnica en lugar de las técnicas que buscan la lateralización de una cuerda vocal se basa en que se obtienen resultados comparables, pero con una menor morbilidad y con un procedimiento más corto y sencillo. Consideramos que otras técnicas de resección como la aritenoidectomía [2, [18][19][20] son más agresivas y mantienen una tasa de complicaciones mayor y otras como la cordotomía pueden no ser suficientemente amplias para obtener un adecuado diámetro glótico en el caso de pacientes con laringes estrechas o necesitar de procedimientos bilaterales lo que puede dificultar la cicatrización o producir un mayor número de eventos aspirativos [3]. Respetar la integridad de los aritenoides y de la comisura posterior así como de las estructuras supraglóticas disminuye la tasa de posibles complicaciones [21,22].…”
Section: Resultsunclassified
“…La elección de esta técnica en lugar de las técnicas que buscan la lateralización de una cuerda vocal se basa en que se obtienen resultados comparables, pero con una menor morbilidad y con un procedimiento más corto y sencillo. Consideramos que otras técnicas de resección como la aritenoidectomía [2, [18][19][20] son más agresivas y mantienen una tasa de complicaciones mayor y otras como la cordotomía pueden no ser suficientemente amplias para obtener un adecuado diámetro glótico en el caso de pacientes con laringes estrechas o necesitar de procedimientos bilaterales lo que puede dificultar la cicatrización o producir un mayor número de eventos aspirativos [3]. Respetar la integridad de los aritenoides y de la comisura posterior así como de las estructuras supraglóticas disminuye la tasa de posibles complicaciones [21,22].…”
Section: Resultsunclassified
“…The other most important symptom is usually dysphonia. Due to the gap between the VFs, voice quality may be better than in the case of unilateral VF paralysis, but a monotonous voice and speaking pattern characterized by short and hurried words followed by stridor of frequent frequency spectrum is not rare [19]. Dysphagia, aspiration and pain in the neck region may also be seen [3].…”
Section: Discussionmentioning
confidence: 99%
“…In fact the exact mechanism of this condition is not known but it has been suggested that chemical denervation of active CT muscles may produce flaccidity in the VFs (Fig. 1) and cause a minimal increase in glottic section area [9,18,19]. This increase, though minimal, may improve respiratory distress even in patients with life-threatening levels of distress.…”
Section: Discussionmentioning
confidence: 99%
“…In a trial of 20 patients with BVFP randomized between total and partial (resecting the vocal process and anterior body) arytenoidectomies, Yilmaz et al [20] found that neither approach had different results regarding success rate, VHI-30 questionnaire scores, aerodynamic, acoustic analysis, or FOSS. The single distinction found was the length of the procedure: partial arytenoidectomy took 10 minutes longer to perform on average.…”
Section: Discussionmentioning
confidence: 99%